Adding an invasive procedure will not necessarily change treatment or outcome of NSCLC patients with preoperative clinical N1 disease. Issue 4 (5th April 2018) - Decaluwé, Herbert; Dooms, Christophe; De Leyn, Paul; Thomas, Pascal; Rami-Porta, Ramon
We would like to thank A. Addeo and G. Banna for their correspondence with comments on our article entitled "Mediastinal staging by videomediastinoscopy in clinical N1 non-small cell lung cancer: a prospective multicentre study" [1]. In this prospective multicentre study, we found a 25% rate of unforeseen N2 disease after staging and resection, confirming the result of a previous prospective study, similar in size and design, investigating the performance of endosonography in the mediastinal staging of clinical N1 (cN1) patients [2]. However, the sensitivity and negative predictive value of videomediastinoscopy versus endosonography was 0.73 (95% CI 0.54–0.86) versus 0.38 (95% CI 0.18–0.57) and 0.92 (95% CI 0.83–0.97) versus 0.81 (95% CI 0.71–0.91), respectively. We acknowledge the lower accrual than initially projected, which resulted in wider width of confidence interval than aimed for. Nonetheless, with these results we argue that videomediastinoscopy could be the preferred technique of invasive mediastinal staging in patients with cN1 disease, outperforming endosonography in this patient group. In patients with clinical N1 NSCLC, videomediastinoscopy outperforms endosonography as a mediastinal staging tool http://ow.ly/ShP330iWzN2